Effect of permanent sea ice cover and different nutrient regimes on the phytoplankton succession of fjords of the Vestfold Hills Oasis, eastern Antarctica - Andrew McMinn; N Bleakley; K Steinberner; D Roberts; Louise Trenerry (2000)
Early season phytoplankton communities in both Omega and Taynaya Bays are characterized by diatoms sedimenting out of the overlying sea ice. Initial nitrate, phosphate and silicate levels are high and the bay waters are covered with ice and well mixed. In Taynaya Bay the ice cover is retained throughout the season while Omega Bay is ice free for 6-8 weeks. After ice break out in Omega Bay, the phytoplankton community changes from one dominated by diatoms to one dominated by the phytoflagellates, Pyramimonas spp., Cryptomonas sp. and Gymnodinium sp. In Taynaya Bay the ice remained and even though phytoflagellates became more common, diatoms still dominated. These differences in community composition result from differences in light climate, extent of stratification and nutrient levels.